Peningkatan Kemampuan Matematika Melalui Penggunaan Metode Pembelajaran Berbasis Permainan di Sekolah Dasar Negeri 060944 - Adinda Riana Hermawan; Khairunnisya Azzahra; Siti Azahra (Jurnal Bintang Pendidikan Indonesia, 2024)
This research aims to explore the effectiveness of using game-based learning methods in improving the mathematical abilities of students at State Elementary School 060944. The research was conducted using an experimental pre-test post-test control group design, involving two classes with a total of 60 students. One class was the control group and received conventional learning, while the other class was the experimental group and received game-based learning. The research results show that game-based learning is effective in improving students mathematical understanding and skills compared to conventional lerning. The practical implication of this research is the importance of integrating interesting and activity-based learning methods in the learning process at State Elementary School 060944 to improve student academic achievement.